DAPATKAH TRANSFER UANG ANTAR GENERASI MENJELASKAN TREND PARTISIPASI ANGKATAN KERJA LANJUT USIA DI INDONESIA? - Ratu Eva Febriani (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2013)
Changes in population structure leading to the aging of the population is a challenge in development. In Indonesia, the majority of elderly people are still working and most of them are poor. There are limitations as well as the role of government in protecting the lives of the elderly population to encourage a greater role of the family. Intergenerational Transfer is a solution that can be used to maintain the life of elderly people remain prosperous. Using data from Indonesia Family Life Survey (IFLS) in 2007 and the probit analysis technique, this study provides important results to confirm the position of intergenerational transfers in reducing the level of participation of elderly people in the labor market.